Petőháza Község Önkormányzata gazdálkodásának elemzése (2010-2014) - Kámán Bettina (2015)
In recent years the emergence of financing problems and continuous central reforms has brought about a severe situation for local governments. Due to constant changes in law, they were facing unfavourable situations and while their income was falling they had financing problems along with an increasing expenditure. Thus they had to take out a loan, so their debt increased considerably. Within the framework of debt consolidation the state took over the debt of local governments to reduce their indebtedness. It must be highlighted that since 2013 most of the functions of local governments including the running of educational institutions have been taken over by the state. I have examined the administration of finances of the Local Government of Petőháza concerning the past five years by the data of the annual accounts for the 2010-2014 period. In addition, I have studied its operation, legal structure, employees and statutory duties. Furthermore, I have collected information about the village itself and its history. In the first part of my thesis, the concept, forms, duties of the local government and its place in the public finance are described. For the description I have studied specialized literature. In analysing the administration of finances of the local government I also examined the changes in expenditures and revenues, its tendering operations and the change in amount of assets in these five years. For the analysis of the financial condition and assets of the settlement I have used not only the key indicators available but the so-called CLF method which is also used by the State Audit Office of Hungary. This method consistently distinguishes between revenues and expenditures of the budget and their balances as either current or capital. In examining the changes of the local government’s revenues and expenditures, it can be stated that each year, except 2013, the revenues exceeded the expenditures and residual cash was generated every year. Its financial situation and assets can be regarded as stable as the operating income exceeded the expenses. The local government’s short-term solvency, its liquidity is particularly favourable, it can settle the short-term liabilities on time. It did not encounter any problems in financing, it was not in need of taking out a loan. Several investments and renovations were carried out which were financed both from its own source and grants. In my opinion the Local Government of Petőháza can be considered efficient in its administration of finances. Thanks to its constant grow and development, the settlement is becoming more and more attractive both to enterprises and those looking for a place to live.